BOOK REVIEW TITLE: THE IDENTITY POLITICS OF PEACEBUILDING: CIVIL SOCIETY IN WAR-TORN SRI LANKA - Khwairakpam Goutam Singh (Scholar Express Journal, 2021)
The book examines civil society and peace movements in the context of the country's identity-based violent conflict. It explains why civil society organisations working for peace tend to focus on the political sentiments engendered by the pursuit of peace to instil a sense of security in people, rather than challenging the fundamental structure of conflict.
Keywords: Civil society; NGOs; Peace; Actor